Legal Protection Of Foreign Famous Marks That Are Not Registered In Indonesia According To Law Number 20 Of 2016 Concerning Marks And Geographical Indications - Ubaidillah, Nauval; Rahmatiar, Yuniar; Sanjaya, Suyono (Universitas Muhammadiyah Sumatera Utara, 2024)
A brand is a symbol of the identity of an economic product that has a price that encourages producers to continue to compete and innovate in any way so that the brand becomes popular among the public. Brands also contain a promise from the manufacturer to continue to provide certain characteristics, benefits and services to consumers. Brands in Indonesia are regulated in Law Number 20 of 2016 concerning Brands and Geographical Indications, however, brand disputes in Indonesia still often occur even though there is already a law that regulates these marks. Here the author takes the example of the Segovia brand dispute case between Kim Soo Jung, owner of the famous Segovia brand, and Yu Kei Man, an Indonesian citizen (WNI) who created and owns the Segovia brand in Indonesia, in the Supreme Court decision Number 29/Pdt.Sus-Merek/ 2023/PN.Niaga.Jkt.Pst. The method used in this research is normative juridical, namely by examining statutory regulations and legal theory that are related to the dispute issues raised above. The results of this research show that the Supreme Court Decision Number 29/Pdt.Sus-Merek/2023/PN.Niaga.Jkt.Pst. has provided legal protection for well-known foreign brands that were not previously registered in Indonesia, this protection takes the form of canceling the Defendant's Segovia brand from the general list of brands of the Directorate General of Intellectual Property Rights. So well-known foreign brands that have not been registered in Indonesia still receive legal protection so they are protected from people who do not have good intentions with the famous brand.